2020
DOI: 10.1002/ajoc.202000023
|View full text |Cite
|
Sign up to set email alerts
|

Friedel−Crafts‐Type Allylation of Phenol Derivatives Catalyzed by In Situ‐Generated Silyl Cyanometallates

Abstract: We successfully demonstrated that Friedel−Crafts‐type allylation of phenol derivatives and allylic phosphates is catalyzed by the AgTFA/trimethylsilyl cyanide (Me3SiCN) and Pd(OAc)2/Me3SiCN combined systems to afford the C‐allylated product in a highly regioselective manner. The corresponding silyl cyanometallates generated in situ are proposed to be the active catalytic species. Lewis acidity of the reversibly formed ion pairs is appropriately regulated for this reaction. The para‐allylated anisole and phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…We have already reported that a silyl cyanometallate complex (Me 3 Si)­[Ag­(CN) 2 ] was reversibly generated by the reaction of a silver salt and excess amount of Me 3 SiCN . The complex functioned as a stronger silyl Lewis acid than the less polarized Me 3 SiCN …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have already reported that a silyl cyanometallate complex (Me 3 Si)­[Ag­(CN) 2 ] was reversibly generated by the reaction of a silver salt and excess amount of Me 3 SiCN . The complex functioned as a stronger silyl Lewis acid than the less polarized Me 3 SiCN …”
mentioning
confidence: 99%
“…15 The complex functioned as a stronger silyl Lewis acid than the less polarized Me 3 SiCN. 16 In situ generated 7a acts as a precursor of iminium B under the acidic conditions, and it accepts cyanide ( − CN) through Strecker-like reaction mechanisms to afford the cyanomethylated product 2a.…”
mentioning
confidence: 99%